Estiércol y roca fosfórica en el rendimiento de Hordeum vulgare L. var. Zapata en Santiago de Chuco, La Libertad - Rojas Carlos, Marilyn Katerin (2019)
This research work was carried out during the months of February to September of 2018, on a plot located in the Alto Paraíso hamlet; District and Province of Santiago de Chuco, La Libertad. The study aimed to evaluate the effect of sheep manure and phosphoric rock on the performance of Hordeum Vulgare L. var. Zapata in Alto Paraíso, located at 3990 masl. A Random Complete Blocks design was used with a 3 x 3 factorial arrangement with 4 repetitions. The factors studied were 3 levels of manure (E): e0 (0 t.ha-1), e1 (4 t.ha-1); e2 (8 t.ha-1) and 3 levels of Phosphoric Rock (R): f0 (0 kg.ha-1); f1 (333 kg.ha-1); f2 (666 kg.ha-1). To determine the statistical differences between treatments, the analysis of variance and the Tuckey test at 5% significance were performed. The results showed that sheep manure and phosphoric rock affect yield, the number of tillers per plant, the number of spikes per plant, the number of spikes per square meter, the number of grains per spike, the weight of a thousand grains , the length of the spike and the height of the plant in the cultivation of barley var. Shoe in Alto Paraíso, Santiago de Chuco, La Libertad. In addition, it was shown that sheep manure incorporation levels and phosphoric rock doses evaluated do not affect the number of plants per square meter.